Assessing self-regulated learning: The case of vocabulary learning through information and communication technologies. Issue 5 (4th July 2018) - Şahin Kızıl, Aysel; Savran, Zehra
ABSTRACT: Focusing on Self-Regulated Learning, this study aims to contribute a gap in current research by developing a learning environment and domain-specific measure (i.e. vocabulary learning in Information and Communication based environments) that could be used for research and pedagogical purposes in language learning. The development and validation of the instrument underwent an extended test design process. The first phase was the development of an item pool which made use of relevant literature and focus group interviews with EFL learners ( n = 15). The second phase was the field-testing of the measure through its administration to 77 EFL learners. The last phase involved an evaluation of the psychometric properties of the revised instrument given to a total of 250 EFL learners. The findings from Confirmatory Factor Analysis with acceptable values of goodness of fit indices (NFI = .89; CFI = .93; TLI = .92, RMSEA = 0.06 and SRMR = 0.04) supported a 23-item, five-factor scale. The Cronbach alpha internal consistency coefficient of the overall scale was calculated to be .85, leading to the conclusion that the scale proposed here is a valid and reliable measure for systematic inquiry into EFL learners' self-regulated vocabulary learning through technology.